Optimization of Logistics Management and Distribution of Bakery Products at PT. Nippon Indosari Corpindo Tbk Purwakarta - Rhiswandi, Rhandi; Puspasari, Dewi; Djunaedi Rusli, Yus; Putri Mulyani, Indah; Herdianie, Revalina (Journal of Management, 2025)
Logistics management has a strategic role in the processed food industry, especially in products with a limited shelf life such as bread. This study aims to analyze the application of logistics management of PT. Nippon Indosari Corpindo Tbk Purwakarta as a bread producer under the Sari Roti brand. The research method uses a descriptive qualitative approach through direct observation in the factory and informal interviews with company employees. The results of the study show that the company implements a multi-channel distribution system, including an internal fleet, hawker system, as well as cooperation with modern and traditional retail networks. The First In First Out (FIFO) strategy is applied in warehouse management to maintain product freshness, while the distribution information system helps monitor the flow of goods in real time. The main obstacle lies in high logistics costs and limited shelf life, so optimizing distribution routes and utilizing digital technology is an urgent need. These findings confirm that effective logistics management integration can improve operational efficiency, expand market reach, and strengthen the company's competitiveness in the bakery industry in Indonesia.